INOVASI MODEL DESAIN UNIVERSAL UNTUK PEMBELAJARAN KEBUTUHAN KHUSUS DI PERGURUAN TINGGI - Yoga Dwi Windy Kusuma Ningtyas; Fitri Amilia; Nur Kamilah (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2020)
The present study is aimed to describe the development of an innovated learning for the disabled students in higher education. The development of learning innovation was performed by developing a learning model, that is what so-called Universal Design model (DUE). The method implemented to develop the model was Research and Development). This method constitutes several stages, among others: 1) needs analysis, 2) gathering information, 3) designing a product, 4) validating the product, 5) revising the product, 6) trying out the product, 7) revising the product, and 8) consolidating the product. The result of the research shows that the produc, in this case is DUE learning model, has met the criteria after going through several tests from the experts, thus valid.